Nano-Structured Lignin as Green Antioxidant and UV Shielding Ingredient for Sunscreen Applications - Davide Piccinino; Eliana Capecchi; Elisabetta Tomaino; Sofia Gabellone; Valeria Gigli; Daniele Avitabile; Raffaele Saladino (Antioxidants, 2021)
Green, biocompatible, and biodegradable antioxidants represent a milestone in cosmetic and cosmeceutical applications. Lignin is the most abundant polyphenol in nature, recovered as a low-cost waste from the pulp and paper industry and biorefinery. This polymer is characterized by beneficial physical and chemical properties which are improved at the nanoscale level due to the emergence of antioxidant and UV shielding activities. Here we review the use of lignin nanoparticles in cosmetic and cosmeceutical applications, focusing on sunscreen and antiaging formulations. Advances in the technology for the preparation of lignin nanoparticles are described highlighting structure activity relationships.